Parameterization of glacier inventory data from Jotunheimen/Norway in comparison to the European Alps and the Southern Alps of New Zealand - Baumann, Sabine; Winkler, Stefan (ERDKUNDE, 2010)
A parameterization by Haeberli and Hoelzle (1995) was applied to the glacier inventory data of Jotunheimen, Southern Norway, for three distinct time steps: ‘Little Ice Age’ maximum, 1980s, and 2003. Input data are measured or mapped values of the surface area, the length of the glacier flowline, and the minimum and maximum altitude. Additionally, the mass balance gradient and the glacier geometry had to be determined. Data from three glaciers with direct mass balance measurements available were applied to evaluate the parameterization results. According to the data, the area could be separated in a more maritime western and a more continental eastern part. These results were compared with existing parameterization results for the European Alps (Haeberli and Hoelzle 1995) and the Southern Alps of New Zealand (Hoelzle et al. 2007), and for the time period from the ‘Little Ice Age’ maximum until the 1970s/80s. The area loss was largest in New Zealand (-49%), moderate in the European Alps (-35%), and lowest in Jotunheimen (-27%). The corresponding volume loss was about 61% for New Zealand, 48% for the European Alps, and 42% for Jotunheimen. Jotunheimen, therefore, is the most continental of these three regions.